2020
DOI: 10.3390/toxins12040234
|View full text |Cite
|
Sign up to set email alerts
|

Protein-Bound Uremic Toxins in Hemodialysis Patients Relate to Residual Kidney Function, Are Not Influenced by Convective Transport, and Do Not Relate to Outcome

Abstract: Protein-bound uremic toxins (PBUTs) are predominantly excreted by renal tubular secretion and hardly removed by traditional hemodialysis (HD). Accumulation of PBUTs is proposed to contribute to the increased morbidity and mortality of patients with end-stage kidney disease (ESKD). Preserved PBUT excretion in patients with residual kidney function (RKF) and/or increased PBUT clearance with improved dialysis techniques might improve the prognosis of patients with ESKD. The aims of this study are to explore deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 73 publications
(91 reference statements)
2
38
0
1
Order By: Relevance
“…Similar nding reporting a positive correlation between urea levels (represent the protein intake) and microbiota diversity supports this claim [32]. Furthermore, a high-protein intake increases the plasma levels of protein-bound uremic toxins and urea in healthy individuals [33] and ESRD patients [34]. Thus, high-protein intake may increase gut microbiota diversity.…”
Section: Discussionsupporting
confidence: 59%
“…Similar nding reporting a positive correlation between urea levels (represent the protein intake) and microbiota diversity supports this claim [32]. Furthermore, a high-protein intake increases the plasma levels of protein-bound uremic toxins and urea in healthy individuals [33] and ESRD patients [34]. Thus, high-protein intake may increase gut microbiota diversity.…”
Section: Discussionsupporting
confidence: 59%
“…However, a post-hoc analysis of the HEMO trial, which recruited 1273 participants with a median observation time of 2.3 years, failed to demonstrate a linear association between serum levels of PCS and IS and cardiovascular outcomes in dialysis patients [ 18 ]. Moreover, a study by van Gelder MK et al with 80 participants with dialysis who were followed for a median time of 4.3 years showed that the continuous forms of serum IS and PCS had no significant associations with all-cause mortality and CV events [ 17 ]. Therefore, the PBUTs seem to have no significantly linear association with CV events in dialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have reported neutral findings regarding the relationship between PBUTs and clinical outcomes, including all-cause mortality and CV events in patients with CHD [ 17 , 18 ]. A reverse epidemiology finding linked to protein–energy wasting in dialysis patients has been reported [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Evidences indicates that HDF is superior to conventional hemodialysis therapy for recovery of endothelial function, likely due to a broader clearance of uremic toxins [ 186 , 187 ]. Despite of similar removal of protein-bound uremic toxins, HDF provides superior removal of low-molecular weight protein when compared to high-flux-hemodialysis [ 188 , 189 ]. Among the three main options for convective dialysis therapies, post-dilution HDF has been reported to be more effective than pre-dilution HDF and pre-dilution hemofiltration for the removal of uremic toxins [ 190 ].…”
Section: Therapeutic Strategies For Uremic Toxinsmentioning
confidence: 99%
“…Finally, as uremic toxins levels has been related to residual kidney function in dialysis patients [ 189 , 194 ], its preservation is ultimately an important therapeutic approach for a better control of uremic toxins levels. Even though these results are promising, they should be interpreted with caution.…”
Section: Therapeutic Strategies For Uremic Toxinsmentioning
confidence: 99%